Electrochemical reaction and surface chemistry for performance enhancement of a Si composite anode using a bis(fluorosulfonyl)imide-based ionic liquid. Issue 39 (16th September 2016) - Shobukawa, Hitoshi; Shin, JaeWook; Alvarado, Judith; Rustomji, Cyrus S.; Meng, Ying Shirley
Abstract : A Si composite anode with the ionic liquid electrolyte EMIFSI shows superior rate capability. The decomposition products of EMIFSI are significantly different from those of carbonate electrolytes. Abstract : An ionic liquid (IL) electrolyte with 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIFSI) is applied to a silicon (Si) composite anode for Lithium-ion batteries (LIB). Si is one of the most promising anode materials for LIBs and fluoroethylene carbonate (FEC) has been widely used as an electrolyte additive with Si anodes to enhance electrochemical performance. However, the effect of FEC only lasts for a limited number of cycles. To overcome this issue, a bis(fluorosulfonyl)imide (FSI)-based IL is studied as a potential electrolyte candidate for a Si composite anode. Its effects on the electrochemical performance and the corresponding solid electrolyte interphase (SEI) formation on the Si composite anode are not well understood. This work addresses the correlation between the electrochemical performance and SEI formation to probe the surface chemistry on the Si composite anode. We find that the FSI-based electrolyte provides a stable and reversible capacity in long term cycling tests. This electrolyte has excellent rate capability compared to that of carbonate-based electrolytes. The decomposition products of these electrolytes on Si anodes are investigated by X-ray photoelectron spectroscopy. These results show that the chemical composition on the surface of the Si anode is largely different when using the FSI-based electrolyte than it is when using carbonate type electrolytes. The decomposition products of the IL lead to a large number of inorganic species such as LiOH and Li2 O, which yield superior rate capability for the IL electrolyte. The FSI-based IL offers promising applicability for a practical Si composite anode.